(untitled) (Journal of Naval Architecture and Marine Engineering, 2012)
The effects of temperature dependent thermal conductivity on natural convection flow of an electrically conducting fluid along a vertical flat plate with heat generation have been investigated in this paper. The governing equations with associated boundary conditions for this phenomenon are converted to dimensionless forms using a suitable transformation. The transformed non-linear equations are then solved using the implicit finite difference method. Numerical results of the velocity and temperature profiles, skin friction coefficient and surface temperature profiles for different values of the thermal conductivity variation parameter, Prandtl number and heat generation parameters are presented graphically. Detailed discussion is given for the effects of the aforementioned parameters. DOI: http://dx.doi.org/10.3329/jname.v9i2.9025 Journal of Naval Architecture and Marine Engineering 9(2012) 113-122